Still: A Screenplay Exploring Death Anxiety - The Fear of Losing a Loved On - Maria Olivia Laurent (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The fear of death has long plagued people for its unknown implications and the burden of grief that comes with it; however, it is not something that people often acknowledge. This work intends to highlight that fear-related issues should not be understated as trivial negative emotions and need more awareness. Using the death anxiety and protection motivation theories, I discovered that there are hidden conflicts behind death anxiety that people need to address to minimize their symptoms and eventually undergo a successful coping process. The story follows the struggle of Sasha, who initially rejects her beloved Kaiser’s death by creating alternate universes to save him but then slowly realizes that her interferences are harmful. In the end, she finally accepts his death and moves on. Through that angle, this work aims to motivate people that while death happens inevitably, they can always handle their fear through a more positive mindset. Keywords: death anxiety, codependency, coping, science fiction, dark fantasy, alternate universes